1982
DOI: 10.1128/jb.149.1.79-91.1982
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of DNA-linked RNA in the initiation of Bacillus subtilis chromosome replication

Abstract: After thermal denaturation, an in vivo-labeled RNA was found in a temperature-sensitive initiation mutant of Bacillus subtilis (dna-37) associated with highmolecular-weight DNA. This RNA could be clearly distinguished from other RNA species by different techniques of separation, such as Sepharose 2B filtration, chromatography on nitrocellulose, and equilibrium centrifugation in density gradients. It was obtained even when HCHO was present during denaturation and chilling of nucleic acids and was still detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Both drug inhibition studies and the study of mutants have shown that RNA synthesis is needed for the initiation of DNA replication (87,127,259,260). DNA-RNA complexes have been found in both E. coli and B. subtilis that differ from the RNA found linked to Okazaki fragments during DNA replication.…”
Section: Major Events Of the Bacterial Cell Cyclementioning
confidence: 99%
“…Both drug inhibition studies and the study of mutants have shown that RNA synthesis is needed for the initiation of DNA replication (87,127,259,260). DNA-RNA complexes have been found in both E. coli and B. subtilis that differ from the RNA found linked to Okazaki fragments during DNA replication.…”
Section: Major Events Of the Bacterial Cell Cyclementioning
confidence: 99%